2021
DOI: 10.3390/app11167545
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Population Structure of the Copepod Temora turbinata (Dana, 1849) in the Kuroshio Current Edge, Southeastern East China Sea

Abstract: The abundance of adult males, females, and copepodites, and sex ratio of a Temora turbinata population and seawater hydrology were studied from 2018 to 2019 in waters off northeast Taiwan, northwest Pacific Ocean. The hydrological parameters showed significant differences between sampling months caused by interactions of Kuroshio, East China Sea water, and the China Coastal Current. The highest average abundance was recorded from the June 2018 cruise with 2903.92 ± 3499.47 (inds. m−3), followed by a cruise in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Due to the short life span characteristics, the abundance of copepodites commonly accounts for 21–47% of the total zooplankton abundance and 59.77% to 90.82% of the total copepod abundance in field campaigns [ 78 , 79 , 80 ]. In the present study area, Wang et al reported that the copepodites of the dominant species T. turbinata accounted for 27.29% to 60.30% of the total Temora abundance throughout the year [ 56 ]. In the present study, calanoid copepodites represented the most dominant group, which accounted for 28.06% of the total average copepod abundance with an OR of 100%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the short life span characteristics, the abundance of copepodites commonly accounts for 21–47% of the total zooplankton abundance and 59.77% to 90.82% of the total copepod abundance in field campaigns [ 78 , 79 , 80 ]. In the present study area, Wang et al reported that the copepodites of the dominant species T. turbinata accounted for 27.29% to 60.30% of the total Temora abundance throughout the year [ 56 ]. In the present study, calanoid copepodites represented the most dominant group, which accounted for 28.06% of the total average copepod abundance with an OR of 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Stations around Keelung Island were controlled by northeast monsoon-derived water masses characterized by the following indicator species: T. turbinata , C. elliptica , and C. pauper . The meso-epipelagic T. turbinata , which was the dominant species in the research area, is considered an indicator species of warm water masses and is widely distributed in tropical, subtropical, and temperate areas [ 35 , 50 , 56 , 82 ]. Tseng et al [ 82 ] demonstrated that C. elliptica significantly and negatively correlated with seawater temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temora turbinata is regarded as the predominant species in mesozooplankton communities in various environments around the world. It is able to adapt to various habitats, such as eutrophic lagoons, polluted and eutrophicated waters, outfall areas, and nuclear power plant discharge areas (Hsu et al, 2008;Tseng et al, 2011;Wang et al, 2021). In particular, T. turbinate and Karenia brevis can co-occur in the Gulf of Mexico.…”
Section: Discussionmentioning
confidence: 99%